Preliminary characterization of pathogen-detection activities of serum antibodies from the banded houndshark Triakis scyllium. (November 2021) - Kondo, Hidehiro; Fujimura, Takumi; Murotani, Fuyuka; Yazawa, Ryosuke; Tani, Reoto; Hirono, Ikuo
Abstract: Antibodies of cartilaginous fish are of scientific interest due to their phylogenetic position. In the present study, we developed antiserum against IgM of the banded houndshark, Triakis scyllium, and characterized binding activity of the IgM against fish pathogenic bacteria. Pentameric and monomeric IgM antibodies were separated by gel filtration chromatography using high performance liquid chromatography and SDS–PAGE. Antisera were developed by immunizing rabbits with unfractionated IgM antibodies separated by SDS–PAGE electrophoresis. Shark serum antibodies were found to have binding affinity for Aeromonas hydrophila, Vibrio anguillarum, Edwardsiella tarda, and Pseudomonas plecoglossicida antigens but not Lactococcus garvieae by enzyme-linked immunosorbent assay. We speculate the binding activities of shark antibodies may confer protection against certain bacterial pathogens. Highlights: The pentameric and monomeric Igs of the banded houndshark were separated by HPLC and SDS-PAGE. Antiserum against the Igs was developed. The shark immunoglobulin bound to certain fish pathogenic bacteria.